Studies on physico-chemical and microbiological qualities of some selected brand of mango fruit juice of Bangladesh - Amin, Md. Ruhul (BRAC University, 2016)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology.